AB0194 Ll-37: A New Marker for Interstitial Lung Disease (ILD) in Systemic Sclerosis (SSC)?. (10th June 2014) - Hizal, M.; Bruni, C.; Romano, E.; Mazzotta, C.; Guiducci, S.; Tufan, A.; Matucci Cerinic, M.
Abstract : Background: Fibrosis of the skin and visceral organs is the hallmark of SSc and ILD is the leading cause of SSc related morbidity and mortality [1]. LL-37 peptide is the only cathelicidin of the human antimicrobial peptide family with antimicrobial effects and an immunomodulatory activity [2]. LL-37 was shown to decrease with age [3]. Recent data defined its anti-fibrotic effects on dermal fibroblasts and anti-apoptotic effects on SSc dermal fibroblasts [4]. Objectives: To investigate the association between SSc related ILD and circulating levels of LL-37. Methods: SSc patients and healthy controls aged 18-80, without signs or symptoms of systemic infection. Clinical data, autoantibody panel and internal organ assessment results (echocardiogram, esophageal manometry, chest HRCT, Lung Function Tests, Capillaroscopy). The pulmonary involvement was defined as SSc related ILD appearance on HRCT scans like ground-glass, reticular and honeycomb pattern. For the measurement of the LL-37 (Hycult Biotech) levels from blood samples of the patients ELISA has been used. Statistical analysis was performed with association/correlation test as appropriate. Results: 58 SSc patients were enrolled and divided into 1.patients with pulmonary involvement (n=30), 2. patients without pulmonary involvement (n=28). 28 healthy subjects were used as controls. LL-37 concentrations were remarkably lower in SSc patients with ILD vs SSc patients without ILD (1, 3575 ng/ml vs 4, 6175 ng/ml, p=0, 035) and control subjects (1, 3575 ng/ml vs 5, 5300 ng/ml, p=0, 009). In SSc patients without pulmonary involvement, LL-37 serum levels were not different from controls (p=0, 812). No association was found between LL37 circulating levels and any of the other clinical, laboratory or instrumental parameter recorded. Conclusions: Significantly lower levels of LL-37 were observed in patients with SSc-ILD. Our results suggest that reduction of the levels of the peptide may be associated to the development of ILD. It remains to be tested in larger SSc cohorts if the circulating levels of LL-37 might be used as an indirect marker of ILD. References: Bussone G, Mouthon L. Interstitial lung disease in systemic sclerosis. Autoimmunity reviews. 2011;10(5):248-55. Vandamme D, Landuyt B, Luyten W, Schoofs L. A comprehensive summary of LL-37, the factotum human cathelicidin peptide. Cellular immunology. 2012;280(1):22-35. Alvarez-Rodriguez L, Lopez-Hoyos M, Garcia-Unzueta M, Amado JA, Cacho PM, Martinez-Taboada VM. Age and low levels of circulating vitamin D are associated with impaired innate immune function. Journal of leukocyte biology. 2012;91(5):829-38. Kim HJ, Cho DH, Lee KJ, Cho CS, Bang SI, Cho BK, et al. LL-37 suppresses sodium nitroprusside-induced apoptosis of systemic sclerosis dermal fibroblasts. Experimental dermatology. 2011;20(10):843-5. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2948